Pengaruh Price Dan Taste Terhadap Loyalitas Pelanggan Pada Konsumen Xiboba Jl Dr. Mansyur Medan - Savira, Shinta Aulia; Lestari, Indawati (Universitas Medan Area, 2024)
The purpose of this study was to determine the Effect of Price and Taste on Customer Loyalty at Xiboba Jl. Dr. Mansyur Medan. The type of research used is associative, using a quantitative approach. The sample criteria to be used in this study are: Consumers who make purchases of drinks at Xiboba more than three times or consumers who consistently buy Xiboba drinks. Determination of the number of samples in this study using the Slovin formula The population in this study was taken from the results of sales data for three months from June - August, which is 1500. The sampling technique used is purposive sampling technique with the sampling criteria method. The criteria used are consumers who make purchases of Xiboba more than three times Based on the criteria, 94 samples were obtained. The type of data used in this study is quantitative data with primary data sources, and interview data collection techniques and questionnaire distribution. The data analysis technique used is multiple linear regression analysis with the help of SPSS Version 25. The results of the study showed that partially Price has a positive and significant effect on Customer Loyalty at Xiboba Jl. Dr. Mansyur Medan, and Taste has a positive and significant effect on Customer Loyalty at Xiboba Jl. Dr. Mansyur Medan. The results of the simultaneous test show that Price and Taste have a positive and significant effect on Customer Loyalty at Xiboba Jl. Dr. Mansyur Medan.